Perioperative complications following major vascular surgery. Correlations with preoperative clinical, electrocardiographic and echocardiographic features - Dimitri Tsialtas,; Maria Giulia Bolognesi,; Stephania Assimopoulos,; Matteo Azzarone,; Riccardo Volpi,; Roberto Bolognesi, (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: We investigated the incidence rate of perioperative complications following major vascular surgery, as well as identified the risk factors and preoperative clinical, electrocardiographic and echocardiographic determinants, related to these complications.Methods: We studied 241 patients with asymptomatic intact abdominal aortic aneurysm (AAA) subjected to open surgical repair, 182 with critical carotid stenosis subjected to endarterectomy (CEA), and 158 with severe symptomatic occlusive peripheral artery disease subjected to aortofemoral bypass (AFB). Preoperatively, all subjects provided a medical history and underwent physical, laboratory examinations, a standard ECG, and transthoracic echocardiography.Results: Overall, the perioperative mortality rate was 1.2%. The highest rate of complications was observed in the AAA group (p